Inside Paremoremo - McCarthy, Christine (Architectural History Aotearoa, 2022)
The idea of imprisonment, which substantially dates from the mid-eighteenth-century, is both integral to many societies today and fervently challenged, as criminological research has unquestionably demonstrated that prisons do not effectively achieve aims of protecting society, nor reform or rehabilitation. Over the last 50 years, the history of our prison architecture is bracketed by the building of Paremoremo (in the aftermath of the 1965 Mt Eden prison riot) and the more recent adoption of the American-derived New Generation prisons (e.g. Auckland Central Remand (2000), Mt Eden Corrections Facility (2011), and Kohuora (Auckland South Corrections Facility), Wiri (2015)). Paremoremo (1963-1969; archt: J.R.B. Blake-Kelly), was, at the time, "arguably the most modern and technologically sophisticated gaol in the world." It was influenced by the designs of: Blundeston prison, Suffolk, England (1961-63); Kumla prison, Sweden (1965); and Marion prison, Illinois (1963). The New Generation prisons interiorised the thinking behind 1960s campus-style prisons that displaced the cell to primarily nocturnal habitation. This paper will consider the historical consequences of 1960s prison design and Paremoremo on New Zealand prison architecture.